Effect of Nitrogen and Silicon on Rice Submerged at Tillering Stage. (1st January 2018) - Chu, Meijie; Liu, Ming; Ding, Yanfeng; Wang, Shaohua; Liu, Zhenghui; Tang, She; Ding, Chengqiang; Chen, Lin; Li, Ganghua
Abstract : Core Ideas: Basal silicon promotes rice growth and development at the tillering stage. After flooding, foliar spraying N or silicon timely had a better effect. Foliar spraying N had more advantages than silicon. Flooding is a major threat to rice ( Oryza sativa L.) yields. We wondered if basal Si and foliar spraying fertilizer had an influence on rice submerged at tillering stage. The results showed that basal Si application promoted rice growth and development at the tillering stage, improving rice seedling tolerance to submergence stress. After the occurrence of flooding, timely foliar spraying of N or Si had significant remedial effects, and spraying N along with Si had a better effect. The combination of basal Si and post‐flooding N and Si spraying was the most promising method of nutrient application and as resistance to damage during submergence was enhanced, plants rapidly resumed growth and development. By maintaining a great number of green leaves and tillers as well as higher aboveground and belowground dry mass, sugar contents and antioxidant enzyme activities, these plants yielded significantly more grain. We conclude that reasonable use of Si leads to resistance and alleviation of the damaging effects of submergence and contributes to reducing yield losses in rice.